THE USE OF CONTRACEPTION IN COUPLES OF REPRODUCTIVE AGE DURING THE COVID-19 PANDEMIC IN INDONESIA : LITERATURE REVIEW - Nurmalia Ermi (Avicenna: Jurnal Ilmiah, 2021)
Background: The use of contraception is one of the benchmarks for the success of family planning programs. The COVID-19 pandemic has had an impact on people to limit activities outside the home. The appeal from the government also has an impact on the possibility of hampering access to family planning services. The delay in family planning services will lead to a decrease in the use of contraception will ultimately have an impact on the uncontrolled birth rate (Baby Boom). The purpose of this study was to see how the use of contraception in couples of childbearing age during the COVID-19 pandemic. Methods: This study is a literature review related to the use of EFA contraceptives during the COVID-19 pandemic through the Google Scholar database, PubMed, government publication data. Results: Contraceptive use among new family planning participants decreased in general as well as among MKJP participants in the NTB area. The prevalence of contraceptive use in Indonesia has increased but has not yet reached the national target of 61.8%. In the DIY region, there was a decrease in contraceptive use among active family planning participants, as well as a decrease in the use of pill and injectable contraception. The research conducted in the Kalimantan region found that most women of childbearing age used the contraceptive method with the highest dropout rate, namely the pill. The number of unmet need for family planning in the NTB area has decreased, but the drop out rate for family planning in the early days of the COVID-19 pandemi has increased. Conclusion: The use of contraception during the COVID-19 pandemi in several regions in Indonesia is still fluctuating, but has a tendency to decrease.